Selected aspects of warmwater fish culture : - Coche, Andre (FAO, 1989)
This book includes many parts: fish culture research institute Szarvas, Hungary; warwater fish hatchery Szazhalombatta, Hungary; Miscellaneous institutions and international personnel Hungary.